Should my NGO go on a “pork barrel diet”? The case of the Priority Development Assistance Fund in the Philippines - Mendoza, Ronald U (Archīum Ateneo, 2014)
Subject area Public Finance Study level/applicability Masters level graduate studies for public and private sector managers. Case overview However, recent reports have surfaced which cast doubts on the accountability and transparency associated with the PDAF of the legislators. Some reports indicate the presence of commissions that NGOs must allegedly pay to the legislators in exchange for their access to the said funds, while a recent scam involves the creation of bogus NGOs that allegedly serve as conduits through which legislators can take advantage of their allocation. The NGO manager needs to decide on whether and to what extent to engage with legislators on tapping the pork barrel funds. She also needs to address the question: “What is the position of my NGO (and possibly all reputable NGOs more broadly) on pork barrel funds moving forward?” Expected learning outcomes The case revolves around the scandal surrounding the pork barrel funds of some legislators that were exposed for apparent abuse in early 2013. The scandal and its repercussions are still ongoing at the time of writing this case, so the authors expect to update this case moving forward. It aims to highlight an example of the role of public institutions and its respective challenges when it comes to critical decisions of keeping public financial a credible undertaking. It is also expected that this case will help develop an understanding of the pros and cons in the use of discretionary funds and help the student identify potential risks for abuse in public finance management with respect to these funds.